G.R.A.S.P.S Strategy: Decreasing Students' Difficulties in Writing Persuasive Text - Stefanie Nike Nurtjahyo; Nur Arifah Drajati; Sumardi Sumardi (International Journal of Language Teaching and Education, 2019)
In literacy, writing becomes an essential component. It becomes the most difficult skill to be learnt because students need to express their ideas and write them accurately. Interesting learning in writing process is expected by them in term of developing their writing skill. This Classroom Action Research shows the students’ ability in exploring their writing skill in the real-world situation by using G.R.A.S.P.S. (Goals, Rules, Audience, Situation, Product/performance, Standards) strategy. This study was carried out in a private school in Surakarta. One class from social program was taken for the sampling. There were 35 students who contributed to the study. Observation, questionnaire, recording, writing assessment reports were used. Findings show that: (1) G.R.A.S.P.S strategy can motivate the students in expressing their ideas; (2) The interesting teaching-learning process in the classroom makes students feel enjoyed because of their roles in real-life situations. It can low pressure in writing; (3) The students also showed their self-confidence. This research is limited to G.R.A.S.P.S. strategy to foster the students in writing persuasive essay.